Specification for decorative contineous laminates based on thermosetting resins (BSI, 1990)
Laminates, Decorative materials, Thermosetting polymers, Polymers, Plastics, Sheet materials, Classification systems, Grades (quality), Surface defects, Defects, Edge, Dimensional tolerances, Marking, Wear resistance, Thermal resistance, Dimensional changes, Impact strength, Cracking, Colour fastness, Workability, Performance, Environment (working), Water absorption, Internal